Recruiting male partners for couple HIV testing and counselling in Malawi's option B+ programme: an unblinded randomised controlled trial. Issue 11 (November 2015) - Rosenberg, Nora E; Mtande, Tiwonge K; Saidi, Friday; Stanley, Christopher; Jere, Edward; Paile, Lusubiro; Kumwenda, Kondwani; Mofolo, Innocent; Ng'ambi, Wingston; Miller, William C; Hoffman, Irving; Hosseinipour, Mina
Summary: Background: Couples HIV testing and counselling (CHTC) is encouraged but is not widely done in sub-Saharan Africa. We aimed to compare two strategies for recruiting male partners for CHTC in Malawi's option B+ prevention of mother-to-child transmission programme: invitation only versus invitation plus tracing and postulated that invitation plus tracing would be more effective. Methods: We did an unblinded, randomised, controlled trial assessing uptake of CHTC in the antenatal unit at Bwaila District Hospital, a maternity hospital in Lilongwe, Malawi. Women were eligible if they were pregnant, had just tested HIV-positive and therefore could initiate antiretroviral therapy, had not yet had CHTC, were older than 18 years or 16–17 years and married, reported a male sex partner in Lilongwe, and intended to remain in Lilongwe for at least 1 month. Women were randomly assigned (1:1) to either the invitation only group or the invitation plus tracing group with block randomisation (block size=4). In the invitation only group, women were provided with an invitation for male partners to present to the antenatal clinic. In the invitation plus tracing group, women were provided with the same invitation, and partners were traced if they did not present. When couples presented they were offered pregnancy information and CHTC. Women were asked to attend a follow-up visit 1 month after enrolment to assess social harms and sexual behaviour. The primary outcome was the proportion of couples who presented to the clinic together and received CHTC during the study period and was assessed in all randomly assigned participants. This study is registered withClinicalTrials.gov, numberNCT02139176 . Findings: Between March 4, 2014, and Oct 3, 2014, 200 HIV-positive pregnant women were enrolled and randomly assigned to either the invitation only group (n=100) or the invitation plus tracing group (n=100). 74 couples in the invitation plus tracing group and 52 in the invitation only group presented to the clinic and had CHTC (risk difference 22%, 95% CI 9–35; p=0·001) during the 10 month study period. Of 181 women with follow-up data, two reported union dissolution, one reported emotional distress, and none reported intimate partner violence. One male partner, when traced, was confused about which of his sex partners was enrolled in the study. No other adverse events were reported. Interpretation: An invitation plus tracing strategy was highly effective at increasing CHTC uptake. Invitation plus tracing with CHTC could have many substantial benefits if brought to scale. Funding: National Institutes of Health.